PSYCHOLOGICAL BARRIERS IN RECEPTIVE SKILLS ACQUISITION - Abdul, Nurdevi Bte (Elite : English and Literature Journal, 2016)
Abstract Listening and reading comprehension involve language specific processes as well as domain-general cognitive abilities – sensation, perception, attention, memory, and reasoning. In comprehending there is sentence processing. It takes place whenever a reader or listener processes a language utterance, either in isolation or in the context of a conversation or a text. This paper is about psychological barriers in receptive skills acquisition, namely listening comprehension and reading comprehension skills. It discussed some psychological barriers that faced by the children in comprehending a language. Those are comprehension disorder in aphasia, dyslexia, slow word level processing, insufficient experience, memory difficulties, mixed receptive-expressive language disorder, auditory processing disorder, and language anxiety. Therefore, it seems imperative for policy makers, planners, curriculum designers, pedagogues and administrators to consider learning barriers so that a proper diagnosis of the barriers, their types can be developed to minimize or remove such barriers. Abstrak Hambatan Psikologis dalam Keterampilan Reseptif Akuisisi. Pemahaman mendengarkan dan membaca melibatkan proses bahasa tertentu serta domain-umum kemampuan kognitif - sensasi, persepsi, perhatian, memori, dan penalaran. Dalam memahami ada pengolahan kalimat. Hal ini terjadi ketika pembaca atau pendengar memproses bahasa, baik dalam isolasi atau dalam konteks percakapan atau teks. Tulisan ini adalah tentang hambatan psikologis dalam pemerolehan keterampilan reseptif, yaitu pemahaman mendengarkan dan pemahaman membaca. Beberapa hambatan psikologis yang dihadapi oleh anak-anak dalam memahami bahasa dibahasa dalam tulisan ini. Hamabatan psikologis yang dihadapi oleh anak-anak dalam memperoleh bahasa yaitu gangguan afasia, disleksia, pengolahan level kata yang lambat, pengalaman yang tidak cukup, kesulitan memori, gangguan campuran bahasa reseptif-ekspresif, gangguan proses pendengaran, dan kecemasan bahasa. Oleh karena itu, penting bagi para pembuat kebijakan, perencana, desainer kurikulum, pendidik dan administrator untuk mempertimbangkan hambatan belajar sehingga diagnosa yang tepat dari hambatan dapat dikembangkan untuk meminimalkan atau menghilangkan hambatan tersebut.